STRENGTH OF COMPOSITE YARN UNDER BIAXIAL LOADING - Soňa Valentová; Vladimír Hrbek; Jan Vorel; Michal Šejnoha (Acta Polytechnica CTU Proceedings, 2018)
The present paper is concerned with two types of periodic unit cell of composite yarn with different geometry but the same material properties. Their macroscopic response under tensile and compressive loading in the transverse direction and their combination are plotted in the graphs. Based on stress-strain curves the failure envelopes are constructed. A simple maximum stress criterion and linear softening law is used in the adopted progressive damage analysis to outline the softening part of stress-strain diagrams. Finally the impact of selected representative volume element is observed through the comparison of results gained for both designed periodic unit cells in the microlevel, meaning the level of yarn.